Regulation of Monospecies and Mixed Biofilms Formation of Skin Staphylococcus aureus and Cutibacterium acnes by Human Natriuretic Peptides - Gannesen, Andrei Vladislavovich; Lesouhaitier, Olivier; Racine, Pierre-Jean; Barreau, Magalie; Netrusov, Alexander I.; Plakunov, Vladimir K.; Feuilloley, Marc G. J. (Frontiers in Microbiology, 2018)
Staphylococcus aureus and Cutibacterium acnes are common representatives of the human skin microbiome. However, when these bacteria are organized in biofilm, they could be involved in several skin disorders such as acne or psoriasis. They inhabit in hollows of hair follicles and skin glands, where they form biofilms. There, they are continuously exposed to human hormones, including human natriuretic peptides (NUPs). We first observed that the atrial natriuretic peptide (ANP) and the C-type natriuretic peptide (CNP) have a strong effect S. aureus and C. acnes biofilm formation on the skin. These effects are significantly dependent on the aero-anaerobic conditions and temperature. We also show that both ANP and CNP increased competitive advantages of C. acnes toward S. aureus in mixed biofilm. Because of their temperature-dependent effects, NUPs appear to act as a thermostat, allowing the skin to modulate bacterial development in normal and inflammatory conditions. This is an important step toward understanding how human neuroendocrine systems can regulate the cutaneous microbial community and should be important for applications in fundamental sciences, medicine, dermatology, and cosmetology.